Explainable machine learning for predicting recurrence-free survival in endometrial carcinosarcoma patients - Bove, Samantha; Arezzo, Francesca; Cormio, Gennaro; Silvestris, Erica; Cafforio, Alessia; Comes, Maria Colomba; Fanizzi, Annarita; Accogli, Giuseppe; Cazzato, Gerardo; De Nunzio, Giorgio; Maiorano, Brigida; Naglieri, Emanuele; et al. (Frontiers in Artificial Intelligence, 2024)
ObjectivesEndometrial carcinosarcoma is a rare, aggressive high-grade endometrial cancer, accounting for about 5% of all uterine cancers and 15% of deaths from uterine cancers. The treatment can be complex, and the prognosis is poor. Its increasing incidence underscores the urgent requirement for personalized approaches in managing such challenging diseases.MethodIn this work, we designed an explainable machine learning approach to predict recurrence-free survival in patients affected by endometrial carcinosarcoma. For this purpose, we exploited the predictive power of clinical and histopathological data, as well as chemotherapy and surgical information collected for a cohort of 80 patients monitored over time. Among these patients, 32.5% have experienced the appearance of a recurrence.ResultsThe designed model was able to well describe the observed sequence of events, providing a reliable ranking of the survival times based on the individual risk scores, and achieving a C-index equals to 70.00% (95% CI, 59.38–84.74).ConclusionAccordingly, machine learning methods could support clinicians in discriminating between endometrial carcinosarcoma patients at low-risk or high-risk of recurrence, in a non-invasive and inexpensive way. To the best of our knowledge, this is the first study proposing a preliminary approach addressing this task.